A method for controlled target strength measurements of pelagic fish, with application to European anchovy (Engraulis encrasicolus). (19th July 2016) - Doray, Mathieu; Berger, Laurent; Le Bouffant, Naig; Coail, Jean Yves; Vacherot, Jean Philippe; de La Bernardie, Xavier; Morinière, Pierre; Lys, Elisabeth; Schwab, Romain; Petitgas, Pierre
Abstract: Measuring fish target strength (TS) in the wild is challenging because: (i) TS varies versus physical (orientation relative to the incident sound wave, size, and depth) and physiological fish attributes (maturity and condition), (ii) the target species and its aforementioned attributes are difficult to assess in near real time, and (iii) in the case of packed fish schools, accepted echoes may originate from multiple unresolved targets. We propose a method for controlled TS measurements of densely packed small pelagic fish during daytime, based on the joint use of a Remotely Operated Towed Vehicle, "EROC", with a pelagic trawl fitted with a codend opening system, "ENROL". EROC, equipped with a 70-kHz split-beam echosounder (Simrad EK60) and a low-light black and white camera, can be moved inside the fishing trawl. Pelagic fish are funnelled into the open trawl and their TS is measured in the middle of the net, where small groups actively swim towards the trawl mouth. The swimming behaviour allows for near-dorsal TS to be measured, minimizing the large effect of incidence angle on TS variability. The EROC camera, located near the open codend, provides optical identification of the species. This method was used to measure the TS of European Anchovy, Engraulis encrasicolus in the Bay of Biscay during 2014 . The mean, near dorsal TS was −43.3 dB, for a mean fork length of 12.5 cm. This value is compared to published values of clupeiforms mean TS obtained for a range of natural incidence angles and discussed in the light of TS modelling results obtained for E. encrasicolus .